Concepts Of Education In Islamic Perspective (Analysis of Al-Qur’an Verse Al-Mujadalah: 11) - Ibnu Rusydi; Mochammad Asep Nurrochmat (Penerbit Hellow Pustaka, 2023)
Basically the meaning of knowledge in Arabic terminology means in-depth knowledge. Knowledge of the nature of things, both sensory and non-empirical supra-sensory issues. This knowledge can be obtained through learning, both formal and non-formal, where the purpose of this is to make humans have a high degree by humans and by Him. For Muslims, science is closely related to belief in the revealed Qur'an and understanding of life and the created universe. Through education, it is hoped that creative people will be born, able to think independently, able to carry out research, discoveries and so on, which attitude is highly recommended in the Al-Quran. The implementation of Islamic education must consider the principles of scientific development in accordance with the instructions of the Qur'an. Education also brings people to be more able to grasp the wisdom behind knowledge, namely the secret of the majesty of Allah Ta'ala, from this it will strengthen the faith, increase worship and noble morals.